The economic costs of mental health‐related discrimination. (August 2016) - Osumili, B.; Henderson, C.; Corker, E.; Hamilton, S.; Pinfold, V.; Thornicroft, G.; McCrone, P.
Abstract : Objective: To estimate and compare the economic costs of mental health‐related discrimination in the domains of health care, relationships and participation in leisure activities in England between 2011 and 2014. Method: A subsample of the Viewpoint survey was interviewed using the Costs of Discrimination Assessment Questionnaire in 2011 and 2014. Information on the impact of discrimination on healthcare use, help seeking from family and friends and participation in leisure activities was recorded. Pattern of contacts, costs and predictor of costs were examined. Results: Our findings showed higher costs of health service use for individuals who reported experiences of discrimination in healthcare settings in 2011 compared with those who did not (mean difference £625, P ‐value 0.019). Individuals who reported experiences of discrimination in relationships in 2014 had higher healthcare costs than those who did not (mean difference £418, P ‐value 0.034). There was some evidence of a reduction in overall levels of healthcare use, leisure activities and support from families over time. Discrimination did not significantly affect help seeking from family/friends or leisure activities. Conclusion: There is some evidence that discrimination is related to increased healthcare costs. A prospective study is needed to better understand the consequences of these effects.